Análise da qualidade ambiental em área de expansão urbana na cidade de Cuiabá - MT - Martins, Yasmine Ibrahim Ali (2022)
The objective of this work is to analyze the environmental quality in an area of urban expansion in the city of Cuiabá. The methodology consisted in the creation of theme maps of land use and coverage within the region of study. These maps were elaborated with the aid of the Geographic Information System (GIS). From this, the crossing of the mentioned theme maps was carried out in order to obtain an environmental quality map of the region. The crossing was performed by overlapping the maps, intersecting the mapping information contained in the attribute tables of each theme map. The generated environmental quality map showed that the study area has, for the most part, good environmental quality indices with the predominance of areas for conservation plus contact with nature, and land coverage classified as non-built-up areas with continuous arboreal vegetation containing fragment of forest. This is due to the fact that the studied area has massive vegetation, mainly near the Córrego do Moinho and the Coxipó River. However, despite the results obtained, it was found that the environmental quality map hides much of the data that was collected in detail in the land use and coverage maps. Thus, it is suggested to use the urban environmental quality map simultaneously with the other maps. This enables carrying out a more detailed analysis and, thus, facilitates the adoption of decision-making based on more complete information.